Training challenges faced by organization in facing globalization : a study at Bank Islam Malaysia Berhad (BIMB) Sabah / Fadhilah Ideris - Ideris, Fadhilah (2010)
Improving training needs at workplaces is important for organizations to continue being competitive in today globalization. Training contributes to competence development in organizations that helps in offering better quality product and services in facing the globalization challenges. This study aims to investigate training challenges that affected towards the competence development of both employee and employer in the context of globalization. The various factors that influences training in a workplaces and the outcome of the said training will also be explored due to the globalization. The study employs by using quantitative survey involving respondents from Bank Islam Malaysia Berhad (BIMB) Sabah branch using self administered questionnaires. A five-point Likert rating scales will be used in order to elicit responses of the participants. The data obtained will then be analyzed using suitable statistics. The finding of this study will reveal the training challenges that contribute towards the employees in the organization in facing the globalization.